Novel insights into the anatomy and histopathology of the sacroiliac joint and correlations with imaging signs of sacroiliitis in case of axial spondyloarthritis - Prati, Clément; Lequerre, Thierry; Le Goff, Benoît; Cortet, Bernard; Toumi, Hechmi; Tournadre, Anne; Marotte, Hubert; Lespessailles, Eric (Frontiers in Physiology, 2023)
For a better understanding of the pathophysiology of spondyloarthropathy (SpA), detailed knowledge of the anatomy of the sacroiliac joint is needed, as sacroiliitis is the earliest and most common sign of SpA and an essential feature for the diagnosis of ankylosing spondylitis. Beyond anatomy, the histopathology of sacroiliac entheses and the immunological mechanisms involved in sacroiliitis are crucial for a better understanding of disease causation. In this narrative review, we discuss the core anatomical, histological and immunohistological observations involved in the development of sacroiliitis, focusing particularly on imaging-based information associated with sacroiliitis. Finally, we try to answer the question whether at the sacroiliac joint, enthesitis precedes synovitis and subchondral bone changes in SpA.